Paparan Media Sosial terhadap Perilaku Seksual Remaja - Mooduto, Siti Fatimah; Abdul, Nurnaningsih Ali; Tompunuh, Magdalena M (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2021)
Internet users are dominated by teenagers, ie 80 percent, with an age range of 15-19 years. The internet is used not only for educational needs but also for entertainment, shopping, social media, and so on. More than 500 million adolescents aged 10-14 years in developing countries have had sex for the first time under the age of 15 years. Increased adolescent sexual behavior has an impact on the high number of underage marriages. This study aims to prove whether there is an effect of social media exposure on adolescent sexual behavior in high school. The research site used is in the first place with the highest number of teenage pregnancies, namely 14 people. This type of research is an analytic survey with a cross-sectional study approach, using a chi-square statistical test. The sample in this study was 40 respondents. The results showed that x 2 calculated the value of p = 0.000 (<0.05), which means that there is an influence of social media exposure on adolescent sexual behavior in high school.